Safety and Efficacy of Ferula asafoetida in Functional Dyspepsia: A Randomized, Double-Blinded, Placebo-Controlled Study. (26th August 2018) - Mala, K. N.; Thomas, Jestin; Syam, Das S.; Maliakel, Balu; Krishnakumar, I. M.
Abstract : Despite the availability of various synthetic drugs for the treatment of functional dyspepsia (FD), the side effects and their cost have always created a great interest in the search for novel natural alternatives for the management of gut disorders. The present contribution reports the safety and efficacy of the kitchen spice asafoetida ( Ferula asafoetida ) in FD for the first time. In the double-blinded, placebo-controlled study, 43 subjects diagnosed to have moderate to severe discomforts of nonulcer FD were randomized to receive hard-shell capsules (250 mg × 2/day) of either placebo (n=22) or a food-grade formulation of asafoetida (Asafin) (n=21) for 30 days. When evaluated by a set of validated indexing tools (GSRS, GDSS, and NDI), almost 81% in the Asafin group showed significant ( p < 0.01 ) improvement in the overall score and quality of life as compared to the placebo. At the end of the study, 66% of subjects in the Asafin group remained symptoms-free. Although the symptoms score improved significantly in both the groups (from -5.67 to -25.29 in Asafin group versus -1.55 to -6.0 in the placebo; p ≤ 0.001 ), the relative percentage of subjects in the Asafin group with more than 80% reduction in various symptoms were: bloating (58%), appetite (69%), postprandial fullness (74%) motion sickness (75%), and digestion (77%) as compared to less than 10% nonspecific improvement in the placebo group. All the subjects remained safe with no adverse events or variations in haematological and biochemical parameters. The study was registered at http://ctri.nic.in/ (CTRI/2018/ 01/011149 ).